Low dose gemcitabine-loaded lipid nanocapsules target monocytic myeloid-derived suppressor cells and potentiate cancer immunotherapy. (July 2016) - Sasso, Maria Stella; Lollo, Giovanna; Pitorre, Marion; Solito, Samantha; Pinton, Laura; Valpione, Sara; Bastiat, Guillaume; Mandruzzato, Susanna; Bronte, Vincenzo; Marigo, Ilaria; Benoit, Jean-Pierre
Abstract: Tumor-induced expansion of myeloid-derived suppressor cells (MDSCs) is known to impair the efficacy of cancer immunotherapy. Among pharmacological approaches for MDSC modulation, chemotherapy with selected drugs has a considerable interest due to the possibility of a rapid translation to the clinic. However, such approach is poorly selective and may be associated with dose-dependent toxicities. In the present study, we showed that lipid nanocapsules (LNCs) loaded with a lauroyl-modified form of gemcitabine (GemC12) efficiently target the monocytic (M-) MDSC subset. Subcutaneous administration of GemC12-loaded LNCs reduced the percentage of spleen and tumor-infiltrating M-MDSCs in lymphoma and melanoma-bearing mice, with enhanced efficacy when compared to free gemcitabine. Consistently, fluorochrome-labeled LNCs were preferentially uptaken by monocytic cells rather than by other immune cells, in both tumor-bearing mice and human blood samples from healthy donors and melanoma patients. Very low dose administration of GemC12-loaded LNCs attenuated tumor-associated immunosuppression and increased the efficacy of adoptive T cell therapy. Overall, our results show that GemC12-LNCs have monocyte-targeting properties that can be useful for immunomodulatory purposes, and unveil new possibilities for the exploitation of nanoparticulate drug formulations in cancer immunotherapy.